Food systems in correctional settings: a literature review and case study - Smoyer, Amy B.; Kjær Minke, Linda (World Health Organization. Regional Office for Europe, 2015)
Food is a central component of life in correctional institutions and plays a critical role in the physical and mental health of incarcerated people and the construction of prisoners’ identities and relationships. An understanding of the role of food in correctional settings and effective management of food systems may improve outcomes for incarcerated people and help correctional administrators to maximize the health and safety of individuals in these institutions. This report summarizes existing research about food systems in correctional settings and provides examples of food programmes in prison and remand facilities, including a case study of food-related innovation in the Danish correctional system. Specific conclusions are offered for policy-makers, administrators of correctional institutions and prison food services professionals,and ideas for future research are proposed.
Keywords: dept.swk

Seeing Through the Eyes of the Other Using Process Recordings - Schneider, Dana A.; Rodriguez-Keyes, Elizabeth; Keenan, Elizabeth King (Clinical Supervision Activities for Increasing Competence and Self-Awareness, 2014)
This chapter describes a two-step process including videotaping and process-recording activities to facilitate self-awareness and the expression of empathy and acceptance toward other points of view. These activities are designed for beginning student clinicians who are currently completing their coursework and their first clinical internship. The first step of videotaping helps clinicians become more aware of their inner thoughts, feelings, beliefs, and personal values. This first step also helps participating clinicians become more aware of their nonverbal communication with clients, helping them assess how their internal experiences of empathy and acceptance match what is being conveyed nonverbally to their clients. The second step of the activity, process recording, helps clinicians reflect on their ability to use self-awareness to analyze their inner experiences and their outer expressions of empathy and acceptance (both verbal and nonverbal) while still being attuned to their clients' communication.
Keywords: dept.swk; nonverbal communication; process-recording activities; self-awareness; videotaping

Group Work Around the Globe: Creating transformative connections in challenging times - Wilkins, Christine; Doel, Mark; Skolnik, Sari; Genke, John; Gardella, Lorrie Greenhouse (Whiting & Birch Ltd, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Coffee Cup - Gardella, Lorrie Greenhouse (Social Work in 42 Objects (and More), 2017)
Can the story of social work be told through Objects? Might a collection of objects be more illuminating than a formal text book or a dry definition? In this engaging, photographic book, Mark Doel curates a collection of 127 objects contributed by people from around the globe to evoke a sense of social work - past, present and future. Written as a Guide to an Exhibition of Social Work, this is the ideal book to introduce social work to newcomers, and to entertain those with long experience of the profession. The objects are presented by a diverse group of people with different perspectives on social work, but with a common imagination.--From publisher.
Keywords: Political Science / Public Policy / Social Services & Welfare; Social Science / Social Work; dept.swk

Introduction to Klaus-Martin Ellerbrock, Theses on Working with Refugees in Germany: Considering the Experiences of Louis Lowy - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Introduction to Olga Derkachova, Children of War: Exploring the Trauma of War through Collective Creative Writing in Literary Workshops - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Migration and HIV among Asian Populations: Social Work interventions - Sen, S; Aguilar, Jemel (Migrant Workers: Social Identity, Occupational Challenges and Health Practices, 2016)
Worldwide labor migration has transformed and reshaped various fields of government policy and professional practices. Labor migration is associated with the non-economic social phenomena that scholars have increasingly paid attention to in both sending and receiving destinations. For practitioners in the field of education, medicine, nursing, social work, mental health, public health, and other professional practices, the human face of labor migration migrant workers and their families daily challenges often reveals the human cost of migration behind the image of economic gain and benefits. Migrant workers and their families are facing vexing challenges ranging from basic needs to psychosocial well-being, despite who they are and where they come from. Traditional ways of thinking and knowing cannot address these challenges adequately; rather, established divisions of professions, systems, disciplines, and/or areas of practice might just be the factor that constrains the ability to clearly articulate compelling problems and adds an additional layer of complexity to problem solving. This book focuses on country policies and practices, and draws on theoretical ideas that provide the intellectual basis. In addition, it offers vivid examples of how migrant workers manage to work, pursue economic security, strive and adjust in new communities, define and negotiate self and identity, and seek health and well-being. While the book illuminates shared challenges and experiences for each group of migrant workers (i.e. low-skilled workers, internal migrants and other types of migrating laborers), it also synthesises the intersectionality across all migrant workers, as they remain committed to bettering the lives of their families and communities in their origin countries as well as new host countries and communities. This volume reflects the efforts of interdisciplinary research and collaboration
Keywords: dept.swk

African Americans and the Consequences of Discrimination - Howe, Esther; Hamilton, Julia (Diversity, Oppression, and Social Functioning: Person-In-Environment Assessment and Intervention, 2010)
Keywords: dept.swk

Lookism: Bias Based on Appearance - Howe, Esther (Diversity, Oppression, and Social Functioning: Person-In-Environment Assessment and Intervention, 2010)
Keywords: dept.swk

Sabbatical Leave Report: Sabbatical Spring, 2015 - Keenan, Elizabeth King (Distribution: Spring ; Social Work., 2015)
From the report: "Project title: Walking the walk or just talking the talk? An exploratory study of the ways social workers understand social work practice." The report describes the research problem, identifies three reserach questions, and discusses the project outcomes and reporting.
Keywords: dept.swk; faculty_collection; sabbatical_report

Group Work: Creating Space for All Voices - International Association for Social Work with Groups International Symposium Chapel Hill, North Carolina); Gardella, Lorrie Greenhouse; Tully, Greg (Whiting & Birch Ltd., 2019)
Keywords: Congresses; Social group work; dept.swk

Walking the Walk or Just Talking the Talk?: An Exploratory Study of the Ways Social Workers Understand Social Work Practice - Keenan, Elizabeth King (2015)
Keywords: dept.swk; faculty_collection

The Common Factors Model for Generalist Practice - Cameron, Mark; Keenan, Elizabeth King (Pearson Education, 2013)
Keywords: Social work administration; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Pearson/Allyn and Bacon, 2011)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Responding to the Oppression of Addiction: Canadian Social Work Perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2010)
"Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community."--pub. desc.
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; faculty_collection; therapy; Social Work; Canada

The Roots of the Recovery Movement in Psychiatry: Lessons Learned - Davidson, Larry (Wiley-Blackwell, 2010)
Keywords: History; Social psychiatry; Community psychiatry; Humanistic psychotherapy; Recovery movement; dept.swk; faculty_collection

Bullying - Howe, E.; Haymes, E.; Tenor, T. (The School Practitioner's Concise Companion to Preventing Violence and Conflict, 2010)
This chapter reviews the most well-researched, evidence-based antibullying interventions: involvement of all the stakeholders in a school, prevention through life skills curricula, problem-solving approaches, and those that focus on rules and consequences. Two factors emerge with clarity: (1) the exact components of the program do not matter as much as the quality and thoroughness with which the interventions are implemented; and (2) given the potentially severe consequences of bullying, it is a moral imperative to continue to implement such programs and to formulate and revise the programs based on solid evidence. © 2008 by Oxford University Press, Inc. All rights reserved.
Keywords: Anti-bullying; Bullies; Bullying; School policy; School safety; School violence; School-based intervention; dept.swk

The importance of housing, neighborhood and community contexts - Allison, K.W.; Broce, R.S.; Houston, A.J. (Adolescent Development and School Achievement in Urban Communities: Resil. in the Neighborhood, 2012)
Keywords: dept.swk

Social work practice with gay men and lesbians within organizations - Appleby, G.A. (Foundations of Social Work Practice with Lesbian and Gay Persons, 2013)
The premise ofthis chapter is that U.S. society will reject continued attempts to defend discrimination against lesbian and gay people in the name of “family values? or “special rights? or “preservation ofmorale? or any other meaningless slogan. Such discrimination will be seen for what it really is: bigotry. However, social change is slow and discriminatory attitudes and behaviors will continue to be oppressive environmental and organizational influences on lesbian and gay social workers employed by human service agencies. This vestige of homophobia and heterosexism, therefore, must become the target of social work intervention (Appleby, 1995). © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.swk

Alcohol Use Among Latino Males: Implications for the Development of Culturally Competent Prevention and Treatment Services - Colon, E. (Alcohol Use/Abuse among Latinos : Issues and Examples of Culturally Competent Services, 2014)
This paper examines the factors surrounding the use of alcohol among Latino males. Prevention and treatment strategies for the provision of culturally competent treatment services are proposed, based on an analysis of the literature. © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.swk

Evolving from an illusionary and self destructive quest for power to a state of empowerment: The curative potential yoga may hold as a vehicle to reclaiming bodily empowerment for women with anorexia - Pizzanello, H.C. (Journal of Sociology and Social Welfare, 2016)
Eating disorders disproportionately afflict women and they are one of the most lethal mental health conditions that practitioners in the field of social work and related mental health fields encounter. Equally alarming is the fact that Anorexia Nervosa is the deadliest of all eating disorders, yet, we are struggling to find an efficacious means of successfully intervening in the treatment and recovery maintenance of anorexia. Drawing from past empirical and theoretical literature, this study explored the potential that the mind body practice of yoga might hold as a complementary therapeutic tool for women struggling to recover from anorexia. The findings that emerged from the analysis of this study’s data indicate that yoga can play a curative role with this population. The findings also revealed that yoga’s primary efficacy resides in its potential to facilitate an experience of connected acceptance and feelings of empowerment in this population of women. © 2016, Western Michigan University. All rights reserved.
Keywords: Anorexia; Feminism; Therapeutic intervention; Yoga; dept.swk; ⛔ No DOI found

Organizational practice with LGBT people - Colon, E. (Social Work Practice with Lesbian, Gay, Bisexual, and Transgender People, 2017)
Keywords: dept.swk

Developing a financial literacy program with survivors of intimate partner violence: The voices of survivors - Stylianou, A.M.; Counselman-Carpenter, E.; Redcay, A. (Social Work (United States), 2019)
As the social work field increasingly recognizes economic abuse within intimate partner relationships, the field has developed financial empowerment programs to empower survivors for their financial future. Although research has demonstrated the effectiveness of financial literacy programs, there are barriers to their implementation in the field. Studies have explored, from the perspective of advocates, best practices in incorporating financial literacy into services; however, no studies have explored implementation approaches from the perspective of survivors. This study explores, from the perspective of 34 survivors, approaches for implementing financial literacy programming. Participants described their understanding of financial empowerment as being in charge of finances, having financial power, and not having to endure the struggle. To counter financial disempowerment, participants identified the need for financial confidence, knowledge, and tools. Participants shared their strategies for saving money, though many participants reported barriers to using banks as savings tools. Almost all participants stressed the importance of financial literacy services for survivors, especially around banking, credit, and debt. Finally, participants shared recommendations for job readiness and training programming. Findings have implications for domestic violence and broader social work organizations implementing financial empowerment services. Social workers can support financial empowerment efforts through program development and research efforts. © 2019 National Association of Social Workers.
Keywords: Adult; Crisis and trauma; Female; Financing, Personal; Humans; Intimate Partner Violence; Literacy; Male; Power, Psychological; Program Evaluation; Qualitative methods; Service delivery; Social Work; Social work practice; Survivors; adult; dept.swk; female; financial management; human; literacy; male; partner violence; peer-reviewed; procedures; program evaluation; psychology; social work; survivor

Group Well-Child Care and Health Services Utilization: A Bilingual Qualitative Analysis of Parents' Perspectives. - Oldfield, Benjamin J; Nogelo, Patricia F; Vazquez, Marietta; Ona Ayala, Kimberly; Fenick, Ada M; Rosenthal, Marjorie S (Maternal and child health journal, 2019)
Objective Alternative primary care structures such as group well-child care (GWCC) may enhance care for families, particularly those subject to structural vulnerabilities such as poverty or restrictive immigration policies. The purpose of this study was to characterize how group dynamics in GWCC impact the perceptions of low-income, immigrant, and/or Spanish-speaking parents of health services. Methods Using Spanish and English interview guides that were conceptually identical, we conducted semi-structured interviews with parents who elected to participate in GWCC at an urban academic center. We drew from directed content analysis, grounded theoretically in the Andersen model of health services utilization. Modeling a bilingual, multicultural analytic strategy, we preserved the narrative of participants in the source language through all stages of analysis. Results From March through August 2017, we interviewed 22 caregivers in their preferred language. Most (82%) were mothers and half spoke Spanish only. Three themes emerged: participants perceived that (1) GWCC facilitates their and their peers' discovery of inherent expertise, which moderates parents' use of health services, (2) GWCC encourages rearrangements of hierarchies of knowledge, professional roles and genders; and (3) in the context of structural vulnerabilities, relationships formed in GWCC facilitate collective efficacy. Conclusions for Practice By considering the self and peer as sources of health-related expertise, GWCC may extend current theoretical models of health services utilization. GWCC provides opportunities to impact health services utilization among families subject to structural vulnerabilities.
Keywords: *Child Health Services/sn [Statistics & Numerical Data]; *Child Welfare; *Parents/px [Psychology]; *Patient Acceptance of Health Care/sn [Statistics & Numerical Data]; Adolescent; Adult; Child Health Services; Child Welfare; Child, Preschool; Cultural diversity; Female; Humans; Interviews as Topic; Interviews as Topic/mt [Methods]; Male; Multilingualism; Parents; Patient Acceptance of Health Care; Patient Acceptance of Health Care/px [Psychology]; Primary health care; Qualitative Research; Qualitative research; Vulnerable populations; adolescent; adult; article; caregiver; case report; child; child care; child health care; child parent relation; child welfare; clinical article; content analysis; cultural diversity; dept.swk; drug efficacy; female; gender; group dynamics; health care utilization; human; human experiment; immigrant; interview; language; lowest income group; male; mother; multilingualism; narrative; patient attitude; peer-reviewed; perception; preschool child; primary health care; procedures; professional standard; psychology; qualitative analysis; qualitative research; semi structured interview; speech; vulnerable population

Feeding relationships: foodways and social networks in a women’s prison - Smoyer, Amy B. (Affilia, 2014)
Research has demonstrated the importance of supportive relationships and social networks to prisoners’ psychosocial outcomes, especially for women. Understandin...
Keywords: dept.swk; peer-reviewed

Dealing food: Female drug users’ narratives about food in a prison place and implications for their health - Smoyer, Amy B.; Blankenship, Kim M. (International Journal of Drug Policy, 2014)
Keywords: dept.swk

Setting the stage: creating study sites that promote the safety and dignity of research participants - Smoyer, Amy B.; Rosenberg, Alana; Blankenship, Kim M. (Social Work Research, 2014)
The U.S. Department of Health and Human Services' (HHS) Code of Federal Regulations regarding Protection of Human Subjects (45 C.F.R. part 46) provides guidance
Keywords: dept.swk

Being on the mat: a process evaluation of trauma-informed yoga for women with substance use disorders - Smoyer, Amy (The Journal of Sociology & Social Welfare, 2016)
Yoga practice is associated with positive health outcomes, including benefits related to managing substance use disorders and trauma symptomology. However, low-income vulnerable communities have limited access to yoga. This process evaluation of a trauma-informed yoga program for women with substance use disorders demonstrates the feasibility and utility of using noncertified yoga instructors to offer a basic yoga in community-based agencies. Participants describe outcomes related to relaxation, mindfulness, and movement that are well-aligned with their recovery needs. Study findings suggest the utilization of instructors with minimal training has the potential to expand research about and access to yoga among marginalized communities. © 2016, Western Michigan University. All rights reserved.
Keywords: Evaluation; Qualitative; Substance use; Women; Yoga; dept.swk; ⛔ No DOI found

Mapping prison foodways - Smoyer, A.B. (Experiencing imprisonment: research on the experience of living and working in carceral institutions, 2016)
Keywords: dept.swk

Fragmented images: how can the eye see itself? A relational and intersubjective reformulation of cross-cultural therapy with cecilia - Pizzanello, Heather (Psychoanalytic Social Work, 2015)
This article discusses why it is crucial in the cross-cultural clinical encounter to practice from both Jessica Benjamin's intersubjective frame as well as relational theory when the therapist is from the dominant White culture and the client is African American. Intersubjective and relational theories are utilized to illustrate how it is in this clinical situation, however, that some therapists may find themselves avoiding the use of a more relational practice. A case illustration is presented from the lens of Winnicott's theory of object relations to convey the dynamic complexities that may impede a therapist from practicing out of these (more relational) frames and then the case is reconceptualized from both a relational and intersubjective perspective. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: Winnicott; cross-cultural therapy; dept.swk; intersubjectivity; peer-reviewed; relational practice

Making fatty girl cakes: food and resistance in a women's prison - Smoyer, Amy B. (The Prison Journal, 2016)
This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cellsall to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the rehabilitative potential of correctional facilities.
Keywords: dept.swk; food; prisoners; resistance; women

Applying research to enhance capacity: A unifying purpose for an integrated profession - Keenan, Elizabeth King (Journal of Social Work Education, 2016)
For more than a century the social work profession has had a dual purpose: to promote individual well-being and social justice, but the micro-macro divide is fragmenting the profession. This article suggests that the profession's aim might best be realized by adopting a unifying purpose, a just sense of well-being. Research on complex adaptive systems conceptualizes a unifying purpose as vertical integration carried out in differentiated ways in discrete moments of practice in various settings. Interpersonal neurobiology and Aristotle's interdependence of character virtues and practical judgment inform a corresponding shift from the dualities of personal and professional to the social worker as a person with differentiated professional capacities and activities. Integration with differentiation enhances capacity to promote the profession's purpose.
Keywords: dept.swk; differentiation; human; human experiment; morality; neurobiology; occupation; peer-reviewed; social justice; social work; wellbeing

Meeting at the thin places: synchronicities in clinical practice - Schneider, Dana A. (Smith College Studies in Social Work, 2016)
Unusual events, beyond mere coincidences, may occur during the course of psychotherapy. Yet, clinical training often does not prepare therapists how to understand and potentially engage with these encounters. The aim of this report is to explore the emergence of synchronistic events in therapy, while providing two clinical case composites to illustrate the author's central points. Drawing on the Celtic concept of thin places, a new understanding of synchronicities and the therapeutic relationship is offered.
Keywords: Internal structure; dept.swk; synchronicity; therapeutic relationship; thin places; unconscious communication; unknown

Home environments, memories, and life stories: preservation of estonian national identity - Rakfeldt, Jaak (Journal of Baltic Studies, 2015)
This paper examines the means by which Estonian national identity was preserved during 50years of Soviet occupation. The study upon which it is based explored such factors as family environments; memories, in the form of oral narratives; and life experiences. This research was informed by the sociocultural approach to mediated action, and it employed both quantitative and qualitative research methods. In 1993, a quota-sampling technique was used to interview a cross section of Estonian society (N=930). Descriptive statistics, and factor and multiple regression analyses were performed. Fifteen qualitative interviews were also conducted. When woven together, these personal histories create a fabric that is representative of the greater Estonian history during the occupation. The implications of these findings may reach beyond the Estonian context to further inform our understanding of the complexities and the vicissitudes of human action.
Keywords: Estonian national identity; dept.swk; life stories; social memory; song festivals; “The Singing Revolution”

Full employment as a permanent policy response to poverty - Tomczak, Stephen Monroe; Rofuth, Todd W. (Journal of Community Practice, 2015)
Rising inequality and concomitant economic insecurity and poverty is a continuing problem in the United States today. Enacting full employment policies would resolve this problem and would serve as a viable poverty reduction strategy. Using a more accurate measure of unemployment such as the Bureau of Labor Statistics U-6 measure would reveal the true unemployment rate. This article provides different strategies, historical and more recent, for enacting full employment with a living wage, particularly the enactment of a permanent national public service employment program administered by the states through the TANF Emergency Fund. Public sector employment expansion in the green or clean economy would benefit the urban unemployed the most. To achieve these ends, social workers, unions and community activists will need to collaborate. Finally, the Federal Reserve should review the history of the relationship between unemployment and inflation rates and develop a more accurate formula for attaining full employment while keeping inflation low. Copyright © Taylor & Francis Group, LLC.
Keywords: United States; dept.swk; economic inequality; emergency; employment; full employment; human; human experiment; peer-reviewed; policy; poverty; social worker; statistics; unemployment

The moderating effect of positive father engagement and accessibility on a school-based system of care intervention for mental health outcomes of children - Bernard, Stanley N; Whitson, Melissa L; Kaufman, Joy S (Journal of Child and Family Studies, 2015)
We conducted an exploratory research study looking at fathering interactions as they relate to the wraparound care given by the Partnership for Kids or PARK Project, a school-based system of care in Bridgeport, Connecticut. The questions posed by our research focused on how fathers' positive interaction measured by their levels of engagement and accessibility can moderate the effect of the school-based system of care intervention on the mental health outcomes of children with serious emotional disturbances. We found that, although not statistically significant, children's access to their father did have a moderating effect on CBCL scores for internalizing behaviors and total problems. There was very small change in CBCL scores for externalizing behaviors. Further, the moderating effect of father accessibility and father engagement had a lasting effect as a moderator through 12 months into the intervention, especially with regard to internalizing behavior scores.
Keywords: Children’s mental health; Fatherhood; Systems of care; dept.swk

Conscious and unconscious use of self: the evolution of a process - Schneider, Dana A; Grady, Melissa D (Psychoanalytic Social Work, 2015)
Recent emphasis has been placed on the central role of the therapeutic relationship in successful treatment. One aspect of the development of an effective relationship is the clinical social worker's use of self. We argue that the use of self happens both consciously and unconsciously and is a dynamic and evolving process in psychotherapy. This evolution can result in the clinical social worker shifting from a stance of doing to being. Drawing from a Japanese tradition of learning, three stages of learning provide a framework for understanding how therapists may transition from a state of doing to being in the therapy. Through this process, the conscious use of self may develop into unconscious use of self. Two case examples demonstrate how expanding and using one's self-awareness and the new knowledge through meaningful learning experiences can shift a clinical social worker's ability to develop and enhance his or her use of self, inviting therapeutic presence and depth. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: conscious; dept.swk; peer-reviewed; therapeutic presence; therapeutic relationship; unconscious; use of self; way of being

“It's the black girls that have the most”: foodways narratives and the construction of race in a women's prison - Smoyer, Amy B (Food and Foodways, 2015)
Prison foodways narratives can expand knowledge about cultural beliefs and perceptions of correctional systems. This exploratory analysis, based in qualitative interview data, seeks to initiate dialogue about the ways in which formerly incarcerated women in the US deploy racialized food narratives when describing the acquisition, preparation, and consumption of prison food. The participants’ food narratives construct prison as a non-white space that is better matched for African-American and Latina women, reinforcing and enacting larger cultural notions about incarceration. This opening analysis calls for more research and deliberation about how prison foodways narratives contribute to understandings about and perceptions of correctional systems and incarcerated people. © 2015, Taylor & Francis Group, LLC.
Keywords: dept.swk

Hunger in a “Land of plenty”: A renewed call for social work action - Libal, Kathryn; Tomczak, Stephen Monroe; Spath, Robin; Harding, Scott (Social Work, 2014)
Keywords: Child; Cooperative Behavior; Cross-Sectional Studies; Financing, Government; Food Assistance; Food Supply; Forecasting; Humans; Hunger; Interdisciplinary Communication; Politics; Poverty; Social Welfare; Social Work; Socioeconomic Factors; United States; catering service; child; cooperation; cross-sectional study; dept.swk; economics; financial management; food assistance; forecasting; human; hunger; interdisciplinary communication; organization and management; politics; poverty; social welfare; social work; socioeconomics; statistics and numerical data; trends

This is common factors - Cameron, Mark (Clinical Social Work Journal, 2014)
Common factors are conditions and processes present in, among, and surrounding participants in clinical work. In the past 20 years, increasing attention and research on common factors has generated a great deal of discussion in clinical psychology, psychiatry, marriage and family therapy, and to a lesser extent, social work. While there is no single definition of common factors, they are generally discussed as the non-technical aspects of therapeutic work-such as the relationship between the practitioner and client and the expectancy of the client-that have been shown to be associated with successful outcomes. Common factors also include attributes of the practitioner and client, the support system of the client, the institutional and organizational conditions in which the practitioner practices, and also the strategic actions employed by the practitioner, client, and all those involved in the work that promote change. This paper will discuss key concepts in a common factors practice perspective and how evidence is used by common factors practitioners, highlight features of common factors practice, and suggest implications for developing a common factors practice approach.
Keywords: Common factors; Evidence; Practice research; Technique; Therapeutic relationship; dept.swk

Beyond the manual: using research and evidence in social work practice - Grady, Melissa D.; Keenan, Elizabeth King (Clinical Social Work Journal, 2014)
There is a growing divide in social work between those that believe social work interventions should be based on either art or science. We argue that these positions create a false dichotomy within the profession, possibly due to the language associated with clinical work and research. In this introduction article of the Special Issue: Beyond the Manual, we outline the debate within social work around the art and science split and then offer a new approach to framing the issue. We argue that social workers are regularly approaching their work with clients using art and science simultaneously and describe a new frame for the profession. In an effort to articulate and promote this new frame, this special issue was born. This introductory article concludes with a brief description of the topics and articles included in the issue to orient the reader to the content included within it.
Keywords: Clinical judgment; Common elements; Common factors; Evidence-based practice, empirically-supported interventions; Research; dept.swk

From silos to scaffolding: engaging and effective social work practice - Keenan, Elizabeth King; Grady, Melissa D. (Clinical Social Work Journal, 2014)
In this final article of the special issue Beyond the Manual: Using Data and Judgment in Clinical Social Work Practice, we extend the discussion regarding the use of data and judgment. We discuss the multiple sources of data used in practice, including research evidence, client perspectives and experience, moment-by-moment process observation, and client feedback regarding progress towards specific, desired outcomes. We move beyond current debates purporting one framework over another to propose a synthesizing framework that situates evidence-based practice, empirically supported interventions and common elements/mapping and adapting practice within a common factors scaffolding framework. This framework provides a way for social workers to effectively make sound judgments using research and client data within the demands of contemporary practice. The article provides a brief overview of the four practice approaches followed by the proposed scaffolding framework and rationale, and concludes with implications for practice, professional education, and research.
Keywords: Common elements; Common factors; Empirically supported interventions; Empirically supported treatments; Evidence-based practice; Research evidence; dept.swk

The effects of cumulative risk and protection on problem behaviors for youth in an urban school-based system of care - Whitson, Melissa L.; Bernard, Stanley; Kaufman, Joy S. (Community Mental Health Journal, 2013)
The present study examined the cumulative effects of risk and protective factors on internalizing and externalizing problems for a sample of youth who were diagnosed with a severe emotional disturbance and enrolled in an urban school-based system of care. The sample included 139 Latino and African American children (ages 5-19; 65 % male) and their families. After controlling for demographic variables, the results of hierarchical multiple regression analyses revealed that cumulative risk and protection were significantly related to internalizing problem behaviors, and cumulative protection was negatively related to externalizing problem behaviors. The findings support the importance of including or increasing strength building approaches, in addition to risk reduction, in order to maximize prevention and intervention efforts for system-of-care populations.
Keywords: Affective Symptoms; African American; African Americans; Child; Child, Preschool; Children's mental health; Cumulative protective factors; Cumulative risk factors; Female; Hispanic; Hispanic Americans; Humans; Internal-External Control; Internalizing and externalizing behavioral problems; Interviews as Topic; Male; Psychiatric Status Rating Scales; Questionnaires; Regression Analysis; Risk; Risk Factors; School Health Services; Schools; Severity of Illness Index; Social Behavior Disorders; Socioeconomic Factors; Systems of care; Urban Population; antisocial personality disorder; article; child; control; dept.swk; emotional disorder; female; human; interview; male; organization and management; peer-reviewed; preschool child; psychological aspect; psychological rating scale; questionnaire; regression analysis; risk; risk factor; school; school health service; severity of illness index; socioeconomics; statistics; urban population

Relationships between child emotional and behavioral symptoms and caregiver strain and parenting stress - Vaughan, Ellen L.; Feinn, Richard; Bernard, Stanley; Brereton, Maria; Kaufman, Joy S. (Journal of Family Issues, 2013)
Children with emotional and behavioral disturbance often have difficulties in multiple symptom domains. This study investigates the relationships between child symptoms and caregiver strain and parenting stress among 177 youth and their caregivers participating in a school-based system of care. Youth were grouped by symptom domain and included those with low scores on both internalizing and externalizing symptoms, those with only high internalizing symptoms, those with only high externalizing symptoms, and those with high symptoms levels in both internalizing and externalizing domains. Results revealed significant group differences on measures of caregiver strain and parenting stress. Caregivers of youth with symptoms in both internalizing and externalizing domains reported the highest levels of strain and stress; however, there was some variation in group differences by caregiver outcome. The results of this study emphasize the importance of providing not only services for youth but also support services for their caregivers.
Keywords: caregiver strain; dept.swk; parenting stress; peer-reviewed; serious emotional and behavioral disturbance

Cultivating curiosity: integrating hybrid teaching in courses in human behavior in the social environment - Rodriguez-Keyes, Elizabeth; Schneider, Dana A (Journal of Teaching in Social Work, 2013)
This study illustrates an experience of implementing a hybrid model for teaching human behavior in the social environment in an urban university setting. Developing a hybrid model in a BSW program arose out of a desire to reach students in a different way. Designed to promote curiosity and active learning, this particular hybrid model has students engage in weekly online activities between their weekly on-ground classes. This article reviews key pedagogical concerns and presents preliminary findings, including student feedback, instructor observations, and strategies for faculty interested in developing such courses. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: dept.swk; education; hybrid; online; peer-reviewed; social work; student perceptions; technology

Being known in undergraduate social work education: the role of instructors in fostering student engagement and motivation - Rodriguez-Keyes, Elizabeth; Schneider, Dana A; Keenan, Elizabeth King (Social Work Education, 2013)
Most undergraduate students pursue a social work major because of their desire to help others. Students tend to be more interested in doing than in understanding the research and knowledge of the profession and the complexities of social work practice. Instructors are often faced with the challenge of enhancing student motivation to learn challenging course material. This study explored student perceptions of instructor influences on their motivation and engagement in learning. Through online surveys, students described their experiences of being known and how those experiences affected their participation in practice, research, and human behavior in the social environment courses. Results showed that instructor caring (providing recognition, expressing relational qualities, and responding to students) positively influences student motivation and affective learning by increasing comfort, willingness to ask questions, take risks, and overall participation. Conversely, of those who reported mixed experiences or who felt unknown, most reported a negative impact on their motivation and participation. These findings suggest that social work faculty can influence student motivation and engagement with essential social work curriculum by expressing care and helping students feel known in the classroom. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: BSW Education; Being Known; Instructor Influence; Motivation; Student Engagement; dept.swk

The impact of a mental health crisis respite upon clients' symptom distress. - Rosen, Jonathan; O'Connell, Maria (Community mental health journal, 2013)
This study examined clients who were admitted to a mental health respite program in the first 3 months of 2011 in order to identify the ability of the program to reduce symptom distress and to explore related psychosocial factors. Participants were provided with self-report questionnaires that included measurements of demographics, mental health status, symptom severity, and program satisfaction. Results indicate a significant improvement in symptom distress (p < 0.05), mental health confidence (p < 0.1), and self-esteem (p < 0.05) from admission to discharge. No change was detected in largely external measurements.
Keywords: *Mental Disorders/pp [Physiopathology]; *Mental Disorders/th [Therapy]; Adult; Community Mental Health Services; Community mental health; Female; Hospital diversion; Humans; Male; Mental Disorders; Mental health respite; Middle Aged; Questionnaires; Surveys and Questionnaires; Symptom distress; United States; adult; article; dept.swk; evaluation study; female; human; male; mental disease; mental health service; middle aged; pathophysiology; peer-reviewed; questionnaire

Revitalizing the vision in supervision: supporting the supervisor in home-based therapy programs - Rodriguez-Keyes, Elizabeth; Gossart-Walker, Sandy; Rowland, Cecilia (Smith College Studies in Social Work, 2012)
Home-based programs provide a growing number of mental health and case-management services to high-risk children, adolescents, and their families. The clinical service providers who work directly with these children and families have varying degrees of education and practice experience as well as a range of different supervisory needs. Because of the daily challenges service providers face, they require support from competent, available supervisors. The professionals who supervise them often assume that responsibility with limited, if any, training in providing supervision. New and experienced supervisors alike often find themselves in positions for which they are ill prepared, without suitable training or administrative support. This article describes a supervision seminar developed for supervisors who supervise the clinicians who provide home-based services. The seminar provides training, support, consultation, and other forms of assistance to help supervisors adapt their clinical skills for use in their supervisory roles.
Keywords: clinical supervision; clinical supervisor; dept.swk; home-based therapy; supervision seminar

The miracle bearers: narratives of birthing women and implications for spiritually informed social work practice - Schneider, Dana A (Journal of Social Service Research, 2012)
Women's childbirth experiences are not widely researched in the social work literature. Therefore, the purpose of this study is to answer questions related to the child-birthing experience. One hundred and nineteen participants responded to a 26-item online questionnaire between April and June 2008, and their written narratives were analyzed using a grounded theory approach. Themes regarding the spiritual dimensions of childbirth emerged from the data and support current research demonstrating the importance of spirituality in women's lives and the meaningful and transformative nature of childbirth experiences. Implications for addressing spirituality in practice when working with childbearing women are explored. Future research that explores how spirituality may function as a protective factor for women with difficult pregnancies, births, and transitions to parenting is recommended.
Keywords: Childbirth; dept.swk; narratives; spirituality; transformation; women

From bumps in the road to the edge of chaos: The nature of change in adults - Keenan, Elizabeth King (Journal of Social Work, 2011)
This article explores the question of how human beings change, how change is constrained, and how change emerges out of and subsequently creates new forms of stability with adults. The emergence of Dynamic Systems Theories (DST) from developmental biology and neuroscience provide the tools to engage in such an understanding by attending to the issues of time, balance, influencing parameters (within person and sociocultural and material environments), and multiple adaptive and maladaptive pathways. DST provides the framework to understand the dynamic processes of bio-psychosocial factors that provide human beings with the stability and the flexibility to navigate the challenges and stressors of living. Complexity, the ability to experience inner continuity as one is changing, is a fluid balance that supports effective functioning. Findings: Key principles and concepts of DST describe multiple pathways of stability and change. A case example illustrates how DST helps social workers understand client experiences and responses to stressors, formulate initial and ongoing assessments, and monitor clients' participation in change activities. Application: Social workers seek to help people who experience an imbalance due to an inability to effectively respond to the negative impact of a stressor. By understanding the various pathways of balance and imbalance along the continuum of continuity to change, social workers can better understand how stressors are impacting specific clients, and subsequently the kinds of change that would best assist each client.
Keywords: change; complexity theory; dept.swk; dynamic systems theory; peer-reviewed; self-organization; stressors

The Roots of the Recovery Movement in Psychiatry - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (John Wiley & Sons, Ltd, 2010)
lessons learned from previous efforts with the goal of "getting it right" this time. In response to the common refrain that we know about and 'do' recovery already, the authors set the recovery movement within the conceptual framework of major thinkers and achievers in the history of psychiatry, such as Philippe Pinel, Dorothea Dix, Adolf Meyer, Harry Stack Sullivan, and Franco Basaglia. The book reaches beyond the usual boundaries of psychiatry to incorporate lessons from related fields, such as psychology, sociology, social welfare, philosophy, political economic theory, and civil rights. From Jane Addams and the Settlement House movement to Martin Luther King, Jr., and Gilles Deleuze, this book identifies the less well-known and less visible dimensions of the recovery concept and movement that underlie concrete clinical practice. In addition, the authors highlight the limitations of previous efforts to reform and transform mental health practice, such as the de-institutionalization movement begun in the 1950s, in the hope that the field will not have to repeat these same mistakes. Their thoughtful analysis and valuable advice will benefit people in recovery, their loved ones, the practitioners who serve them, and society at large. Foreword by Fred Frese, Founder of the Community and State Hospital Section of the American Psychological Association and past president of the National Mental Health Consumers' Association. © 2010 John Wiley & Sons, Ltd.
Keywords: dept.swk

The common factors model: implications for transtheoretical clinical social work practice. - Cameron, Mark; Keenan, Elizabeth King (Social Work, 2010)
Direct practice social workers today are challenged to address the requirements of the complex array of professional, organizational, institutional, and regulatory demands placed on them in the broader socioeconomic context of fewer resources and diminished public support for social welfare services in the United States. The common factors model provides an accessible, transtheoretical, empirically supported conceptual foundation for practice that may help to resolve this conundrum and support effective practice. Common factors are conditions and processes activated and facilitated by strategies and skills that positively influence practice outcomes across a range ofpractice theories. The model provides an expanded conceptualization of the "active ingredients" required for change to include a focus on conditions and processes as well as practice strategies and to focus on all who are involved in the work. The model is described and implications for practice are discussed.
Keywords: *Models, Theoretical; *Social Work/mt [Methods]; Change; Common factors; Empirical; Humans; Professional-Patient Relations; Social Support; Social work practice; Transtheoretical; dept.swk

Navigating the ethical terrain of spiritually focused psychotherapy goals: multiple worldviews, affective triggers, and personal practices - Keenan, Elizabeth King (Smith College Studies in Social Work, 2010)
Constructing mutual, spiritually focused psychotherapy goals is a practice activity fraught with numerous ethical and countertransferential challenges. This article seeks to inform the thinking and enhance the ability of clinical social workers to engage in collaborative and responsive dialogues with their clients regarding the goals of spiritually focused clinical practice by (1) identifying the multiple value frameworks that influence decisions regarding practice goals, (2) articulating some of the ethical complexities and common countertransferential reactions associated with goal setting, and (3) providing self-reflection questions and guides to help therapists navigate the complexities of this material.
Keywords: Countertransference; Ethics; Goals; Piritually focused psychotherapy; dept.swk

Seeing the forest and the trees: using dynamic systems theory to understand “Stress and coping” and “Trauma and resilience” - Keenan, Elizabeth King (Journal of Human Behavior in The Social Environment, 2010)
Although research is beginning to capture the complex interactions of biopsychosocial variables operating within experiences of stressors and trauma, the bodies of research have remained largely separate and limited. This study describes a scaffold of factors and pathways based on principles from dynamic systems theories (DST) to organize the literatures on stress and coping and trauma and resilience. As a process model, DST provides the language to understand both impact and response to stressors and trauma: Not as a list of symptoms but as interactive processes within persons and between persons and their surroundings. © Taylor & Francis Group, LLC.
Keywords: Complexity theory; Dynamic systems theory; Stress and coping; Trauma and resilience; dept.swk; peer-reviewed

Management and Leadership in Social Work: A Competency Based Approach - Rofuth, Todd W.; Piepenbring, Julie M. (Springer Publishing Company, LLC, Springer Publishing Company, 2019)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency, Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

Food in correctional facilities: A scoping review - Smoyer, Amy B. (Appetite, 2019)
In the last 20 years, there has been an exponential increase in research about food in prison. Given this growing interest, it is appropriate to take stock of the field by mapping and synthesizing existing knowledge in order to identify gaps in knowledge and make recommendations for future research. Specifically, the purpose of this scoping review is to understand the experiences of incarcerated people with food in order to inform interventions that will promote positive outcomes for justice-involved individuals and correctional facilities. This review identified 38 peer-reviewed research articles about food in correctional facilities. This sample included qualitative (n = 28) and quantitative (n = 10) research that explored the both the pragmatic and symbolic dimensions of food in these settings. Taken together, this body of research provides a rich description of prison food practices and the implications of these practices on medical, psychological, and sociological outcomes. Moving forward, collaboration between academics, incarcerated people, and correctional practitioners is encouraged in order to develop programs that use this research to improve individual and intuitional outcomes. In addition, while emerging research has begun to develop knowledge about prison food in developing countries, the literature focuses primarily on the US, Canada and Western Europe and there is a need to expand the geographic scope of this inquiry.
Keywords: *Food Services; *Prisons; Canada; Consumer Behavior; Europe; Food Services; Humans; Nutritive Value; Prisons; United States; Western Europe; adult; article; catering service; clinical article; consumer attitude; dept.swk; developing country; female; human; justice; male; nutritional value; peer-reviewed; physician; prison

Social determinants of health: the how, who, and where screenings are occurring; a systematic review - O’Brien, Kyle H. (Social Work in Health Care, 2019)
Screening for social determinants of health allows health care teams to assess and address social factors that influence one’s health, mental health, and access to care. These social factors include poverty, health literacy, social support, exposure to trauma, food insecurity, and housing instability. The objective of this study was to examine what screening tools for social determinants of health are being used, in what contexts, and with what populations. Findings suggest that health literacy is the most commonly screened for, followed by trauma history, social support, food insecurity and housing across diverse contexts and populations. Results from this study can be used to inform providers of available screening tools and resources that can be readily utilized in practice. © 2019, © 2019 Taylor & Francis.
Keywords: Food Supply; Health Literacy; Health Services Accessibility; Health Status Indicators; Housing; Humans; Poverty; Social Determinants of Health; Social determinants of health; catering service; dept.hls; dept.rec; dept.swk; health care; health care delivery; health literacy; health status indicator; housing; human; integrated care; interprofessional practice; peer-reviewed; poverty; primary care; screening tools; social determinants of health

Voices should be heard: what personal stories of homelessness teach us about practice - Schneider, Dana A.; Cretella, Jill; Ranaudo, Sarah; Constantino, Daniel; Cota, Catherine F. (Families in society-The journal of contemporary social services, 2019)
The Voices Should Be Heard community-based participatory research project provided a platform for individuals experiencing homelessness to share their life stories and experiences. Participants offered their reflections on the oppression of homelessness and how the service delivery system could be improved. This article synthesizes these reflections and offers recommendations for practice aimed at reducing the oppression of homelessness and promoting social change. Using a strengths-based perspective, we offer points of entry for working with individuals experiencing homelessness.
Keywords: client-worker relationship; client–worker relationship; dept.swk; homelessness and housing; methods and analytics; modes of practice; peer-reviewed; professional issues; qualitative research; strengths-based practice; subjects of practice; working alliance

Hope, courage, and resilience in the lives of transgender women of color - Ruff, Nadine; Smoyer, Amy; Breny, Jean (The Qualitative Report, 2019)
There is a lack of qualitative and strengths-based knowledge about the lived experience of transgender women of color in the US. To address this research gap, a Photovoice project was undertaken with five transgender women living in a small urban area. Thematic analysis of the participants' discussion of their photographs identified three major themes: Hope, courage, and resilience. Analysis suggests a framework for understanding these women's lived experiences and the psychosocial tools that they use to negotiate their daily lives and persevere in the face of interpersonal and structural oppression. © 2019 Nova Southeastern University. All rights reserved.
Keywords: Courage; Hope; Photovoice; Resilience; Transgender Women; Women of Color; dept.pch; dept.swk; peer-reviewed; ⛔ No DOI found

Understanding the role of the brick-and-mortar classroom in course design and implementation of the “flipped” classroom: An exploratory case study - Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Teaching and Learning with Technology, 2019)
Keywords: dept.swk; peer-reviewed

The Arc of Justice: Examining Policies and Laws to Advance the Human Rights of Transgender and Gender Expansive Children - Redcay, Alex; Counselman-Carpenter, Elisabeth; McMahon, Sheila; Luquet, Wade; Rice, Karen; Lance, Roseanna (Journal of Human Rights and Social Work, 2019)
The role of the social worker in the achievement of human rights is to assist individuals in their struggle for dignity and their attainment of their full potential. Ethical social work ensures just laws and practices that allow all persons to live without discrimination. The purpose of this paper is to present the practice and policy implications of the last five years of court cases regarding transgender and gender expansive (TGE) children and school systems in the USA. This paper outlines the legal justifications for revisions to the current procedures and policies of interacting with TGE children, including use of restrooms consistent with gender identity (RCGI). These recommended guidelines are designed to prevent ongoing human rights violations and create pathways for TGE children to live their lives congruently with their gender identity. Basic human rights for the TGE individual include policy improvements involving restrooms, locker rooms, showers, overnight accommodation, affirmed name, and identification for the child welfare, mental health, educational, medical, juvenile justice, and law enforcement systems. © 2019, Springer Nature Switzerland AG.
Keywords: Ethics; Gender expansive children and youth; Policy; Transgender; dept.swk; peer-reviewed

Provider Attitudes, Organizational Readiness for Change, and Uptake of Research Supported Treatment - Bornheimer, Lindsay A.; Acri, Mary; Parchment, Tyrone; McKay, Mary M. (Research on Social Work Practice, 2019)
Purpose:As implementation and evaluation of research supported treatment (RST) expands across diverse mental health settings, it is essential to understand the facilitators and inhibitors of uptake. The current study examined the relationships between organizational readiness for change, attitudes toward RST, and use of RST among a sample primarily of social workers.Methods:Participants included 158 providers from public child mental health outpatient clinics in the New York metropolitan area. Data were analyzed using structural equation modeling.Results:Use of RST was greater among providers who were younger and had fewer years of professional experience. Both organizational need for change and climate directly and indirectly related to use of RST through attitudes toward RST (partial mediator).Discussion:The organizational context is an important factor that relates to attitudes toward and use of RST in practice. Future research is needed to continue examining factors of RST uptake and sustainability.
Keywords: dept.swk; organizational readiness for change; provider attitudes; research supported treatment; treatment uptake

Teaching note—MSW student perceptions of learning advanced clinical practice skills through the flipped classroom - Counselman-Carpenter, Elisabeth A. (Journal of Social Work Education, 2019)
The flipped classroom, with its focus on student-centered learning and active student engagement, is a growing trend in social work education. This article presents an innovative way of delivering practice content through the flipped classroom model, which can be adapted for any level of social work education. It walks readers through the steps of developing the course and the successes and challenges of the flip, particularly with an incorporated skills lab component. Additionally, this article shares student reflections on the development and execution of the course, with specific feedback on the experiential learning environment, discussions surrounding instructor workload and preparation, and implications for future iterations of the course from students who had very little prior technologically centered learning experiences.
Keywords: dept.swk; peer-reviewed

Older adults’ lived experience of incarceration - Smoyer, Amy B.; Madera, Johanna Elumn; Blankenship, Kim M. (Journal of Offender Rehabilitation, 2019)
This qualitative analysis explores older adults’ lived experiences of incarceration. As part of a larger mixed-methods longitudinal study, 23 older adults were interviewed about their prison and reentry experiences. Findings describe experiences of loss, lack of medical attention, abuse by staff and other inmates, and the uncertainties and danger of prison life. After release, participants reported experiencing anxiety and stress related to their prison experiences. While participants reported that the ability to manage prison life deteriorated with age, some benefits of their senior status were also described. Maturity may allow older prisoners to remove themselves from volatile situations. Participants described experiences of rest and recovery, reflecting coping mechanism and resilience that could improve psychosocial outcomes during and after prison. This descriptive analysis centers the voices of older prisoners and informs interventions to support this vulnerable community.
Keywords: Prison; dept.swk; incarceration; older people; peer-reviewed; qualitative; reentry

Prepared to care: an exploration of continuing education trends of nurses caring for injured children - Roney, Linda Nancy; Acri, Mary C. (Journal of Trauma Nursing, 2019)
The significance of nursing competence in the care of pediatric trauma patients has been well documented. Continuing education for trauma nurses is a critical component of maintaining competence in pediatric trauma care; yet, there is significant variability in the programs and resources used to support this goal. The purpose of this current study was to describe the educational activities that practicing registered nurses engage in to inform their care of injured children. A quantitative, descriptive nonexperimental research design was utilized to describe the educational programs that members of the Society of Trauma Nurses (STN) must complete to work in verified and designated trauma centers. Participants completed a survey instrument that included demographic questions, pediatric trauma educational programs required/offered by their employer, and feedback about pediatric trauma nursing education. A total of 266 STN members completed the electronic survey, reflecting a 9% response rate. Most of the participants reported that the verifying body required trauma nursing education hours (n = 187, 70.3%). The number of required courses ranged from 1 to 6, with 33 (12.4%) reporting this 3-course combination-emergency nursing pediatric course (ENPC), pediatric advanced life support (PALS), and trauma nursing core course (TNCC). The second most common combination of courses (n = 30; 11.3%) was required to take both PALS and TNCC. No significant relationship was found between verifying agency type and continuing education program required (p¿ .05). Trauma nursing core course was the most popular course (n = 208; 79%), followed by PALS (n = 194; 73%) and ENPC (n = 103; 38%). Participants also shared barriers to continuing education activities. It has been 10 years since pediatric trauma nursing course utilization was first explored in the literature. There continue to be significant opportunities to support nurses in continuing education activities related to the care of injured children. While barriers to accessing these types of activities sometimes exist, it is the responsibility of the pediatric trauma community to explore these challenges even further and collaborate with others interested in improving the care of injured children.
Keywords: Child; Child Health Services; Clinical Competence; Education, Nursing, Continuing; Emergency Nursing; Female; Humans; Male; Nursing Staff, Hospital; Pediatric Nursing; Pediatric trauma; Pediatric trauma nursing; Surveys and Questionnaires; Trauma education; Trauma verification; child; child health care; clinical competence; dept.swk; education; emergency nursing; female; human; male; nursing education; nursing staff; pediatric nursing; peer-reviewed; questionnaire

Crowdsourced social work educator technology standards - Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Applying accessibility practices across a curriculum - Marquart, M; Counselman-Carpenter, E (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Case study – teaching online with students who are deaf - Marquart, M; Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Repair the world: Group work in the Deggendorf Displaced Persons Center, 1945-1946 - Gardella, Lorrie Greenhouse (Groupwork, 2019)
This paper explores the formation of a transitory community in the UNRRA Displaced Persons Center in Deggendorf, Germany, where Jewish Holocaust survivors used social group work to preserve their past, to restore humane values, and to prepare for new lives.  Social activism through task groups and activity groups affirmed individual and community self-determination while promoting recovery from trauma.  The experience of the She’erith Hapleitah or “surviving remnant,” as they called themselves, though historically specific, has implications for group work with migrants today.
Keywords: Citizenship; Groupwork; Holocaust survivors; Hope; Migrants; Recovery; Refugees; dept.swk; peer-reviewed

The impact of fluid attraction and fluid identity on mental health - Redcay, Alex; Counselman-Carpenter, Elisabeth; Proctor, Curtis (Journal of Gay & Lesbian Mental Health, 2019)
Using data from the National Longitudinal Study of Adolescent Health, this study examined the impact of sexuality factors and satisfaction with partner on stress, anxiety, and depressive symptoms. Multiple regression was used to evaluate the impact of predictors such as sexuality factors and relationship satisfaction on the dependent variables: stress, anxiety, and depression. Three main results were discovered. First, sexual minority females who have lower levels of education and are dissatisfied with their relationship experience significantly higher stress, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or stress. Second, sexual minority females who have lower levels of education and who are dissatisfied with their relationship experience significantly higher anxiety, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or anxiety. Finally, female sexual minorities who have lower levels of education reported fluid attraction, fluid identity, dissatisfaction with their relationship, and have significantly higher depression when compared to male sexual minorities or heterosexuals. Further research should examine gender and fluidity in greater detail. © 2018, © 2018 Taylor & Francis Group, LLC.
Keywords: Anxiety; depression; dept.swk; fluid attraction; fluid identity; peer-reviewed; satisfaction with partner; sexual orientation; stress

Examining the impact of psychological factors on hospital length of stay for burn survivors: A systematic review - O’Brien, Kyle H; Lushin, Victor (Journal of Burn Care & Research, 2019)
Recovery of burn patients may be impeded by mental health problems. By gaining a better understanding of the impact that psychological factors may have on hospital length of stay, providers may be better informed to address the complex needs of burn survivors through effective and efficient practices. This systematic review summarizes existing data on the adverse psychological factors for the length of burn patients' hospitalization, and assesses the methodological quality of the extant literature on mental health conditions of burn survivors. A literature search was conducted in four electronic databases: PubMed, PsychINFO, Science Direct, and the Cumulative Index to Nursing and Allied Health Literature. Results yielded reports published between 1980 and 2016. Methodological quality was assessed by using an 11-item methodological quality score system. Seventy-four studies were identified by search; 19 articles were eligible for analysis. Findings demonstrate paucity of evidence in the area. Reports indicate longer hospital stay among burn patients with mental health problems. Substance use was the most consistent mental-health predictor of longer hospital stay. Heterogeneity in data on mental health conditions rendered impossible estimation of effect sizes of individual psychological factors on length of hospitalization. Many studies over-relied on retrospective designs, and crude indicators of psychological factors. Findings indicate that mental health problems do have an impact on the trajectory of burn recovery by increasing the length of hospital stay for burn survivors. Inpatient mental health services for burn patients are critically needed. Prospective designs, and more sensitive psychological indicators are needed for future studies.
Keywords: Article; Burns; Hospitalization; Humans; Length of Stay; Survivors; burn; burn patient; burn survivor; dept.hls; dept.rec; dept.swk; distress syndrome; hospitalization; human; length of stay; mental disease; mental health; peer-reviewed; psychological aspect; psychology; substance use; survivor; systematic review

Realizing the potential for leadership in social work - Keenan, Elizabeth King; Sandoval, Silvia; Limone, Christine (Journal of Social Work, 2019)
Ongoing racism, structural inequity, dehumanizing institutional bureaucracies, unresponsive service delivery systems, and gaps in services for emerging needs are just some of the pervasive challenges in need of social work leadership. The multidisciplinary nature of social work practice also requires value-based leadership processes on multiple ecological levels to address the challenges inherent within social delivery systems. Social work encourages all social workers to lead these change efforts, but research on front-line social work leadership is lacking. Constructionist conceptualizations of leadership as social influence processes provide a unit of analysis to examine front-line leadership. A secondary analysis of qualitative data examining social work practice that promotes well-being and social justice revealed leadership processes in multiple social work practice settings. Findings Front-line social workers demonstrate three overarching leadership processes in their practice: challenging injustice and changing mindsets, conduit for change, and organizing resources and relationships. Applications Conceptualizing leadership as social influence processes identifies and acknowledges the leadership of front-line social workers, expanding the profession's capacity to collectively articulate and initiate change with a range of social problems and systemic challenges in organizations and communities.
Keywords: Social work; article; dept.swk; health care delivery; human; leadership; occupation; peer-reviewed; qualitative research; racism; secondary analysis; social constructionism; social justice; social work; social work practice; wellbeing

The Positive Assessment: A Model for Integrating Well-Being and Strengths-Based Approaches into the Child and Adolescent Psychiatry Clinical Evaluation. - Schlechter, Alan Daniel; O'Brien, Kyle H; Stewart, Colin (Child and adolescent psychiatric clinics of North America, 2019)
In traditional medical practice, the diagnostic interview is focused on symptom collection, diagnosis, and treatment. The psychiatric interview is based on the medical model, but mental health clinicians lack the tests found in general medicine. Rapport is the most essential tool for the psychiatrist to uncover symptoms and develop a diagnosis and treatment plan. This article brings a scientific lens to the psychiatric interview. Under this microscope the value of eliciting the patient's well-being at the outset of the interview becomes clear. Using positive psychology, an evidenced-based rationale for the positive assessment is outlined and methodology and practice of the assessment reviewed. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Adolescent Psychiatry; *Child Psychiatry; *Child Welfare; *Mental Disorders/di [Diagnosis]; Adolescent; Adolescent Psychiatry; Assessment; Caregivers; Child; Child Psychiatry; Child Welfare; Common factors theory; Diagnostic interview; Humans; Mental Disorders; Neurosciences; Positive emotions; Positive psychology; Psychiatry; Psychiatry interview; Rapport; Review; Well-being; achievement; adolescent; caregiver; child; child psychiatry; child welfare; clinical evaluation; dept.hls; dept.swk; doctor patient relationship; emotion; human; mental capacity; mental disease; mental health; motivational interviewing; neuroscience; patient assessment; peer-reviewed; priority journal; psychiatry; psychological interview; psychological well-being; reward; social life

“My sister is the one that made me stay above water”: How social supports are maintained and strained when survivors of intimate partner violence reside in emergency shelter programs - Stylianou, Amanda M.; Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Interpersonal Violence, 2018)
While social support is critical in helping intimate partner violence (IPV) survivors heal and build hope, social isolation is a frequent experience for survivors. For survivors residing in domestic violence (DV) emergency shelters, the isolation from social supports is often exacerbated by shelter rules and policies. This study uses a 20th century feminist framework to understand the ways in which social support networks are maintained and/or strained when survivors reside in DV emergency shelters. Among this sample of 76 survivors, 40 participants identified family members as their support system, with siblings and mothers most frequently identified, and 14 participants identified friends as their social support. Prior to entering the DV shelter, survivors reported that their support networks provided encouragement and motivation along with emotional support, financial and material support, and support with children. Participants spoke about the process of informing their support systems of the transition into a DV shelter, the positive and negative impacts of the transition on their support system, and the roles that frequent telephone calls and texts played in maintaining their support networks. Participants reported positive impacts of residing in a DV shelter including improved emotional and physical health, strengthened emotional relationships, and improved physical and emotional resource provision. For those participants reporting negative experiences, they frequently identified logistical barriers, including the inability to receive visitors at the shelter, the distance between them and their friends and family, and strict rules around curfew and child care. Our findings invite researchers and practitioners to consider further examination of best practices around programming that supports survivors in maintaining social supports while residing in shelter programs
Keywords: dept.swk; peer-reviewed

Welcome the stranger: Group work and hospitality in a fearful era - Gardella, Lorrie Greenhouse (Group work around the globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking

Retooling the health care workforce in the era of the Affordable Care Act: An evaluation of an advanced certificate program in integrated primary and behavioral health care - O’Brien, Kyle H.; Acri, Mary C.; Campanelli, Peter C.; Cerniglia, Joseph A.; McKay, Mary M. (Journal of Teaching in Social Work, 2018)
The Affordable Care Act aims to increase affordable coverage, reduce overall costs, and improve health outcomes. To achieve these aims, new knowledge and skills must be built within the existing workforce. The purpose of this article is to examine the behavioral and organizational changes brought about by an educational program that aimed to retool the healthcare workforce for the implementation of integrated primary and behavioral healthcare models, with an added emphasis on prevention. Sixty-three participants of an Advanced Certificate Program completed 1 or more evidence-informed learning modules centered on integrated primary and behavioral health care. The vast majority of students who completed each of the 5 modules of the program reported acquiring new knowledge and skills. Student satisfaction of the program met or exceeded overall expectations. In addition, program participation has resulted in not only students’ intentions to change workplace practices but also actual implementation of workplace changes related to integrated care models. The Advanced Certificate Program appears to be a promising platform for service providers to align their knowledge and skills with the premises of current healthcare reform. © 2018, © 2018 Taylor & Francis.
Keywords: Affordable Care Act; Integrated primary and behavioral health care; certificate programs; dept.rec; dept.swk; integrated care; peer-reviewed; workforce training

An Examination of the Relationship between Maternal Depression and Barriers to Child Mental Health Services - Acri, Mary C.; Bornheimer, Lindsay; Hamovitch, Emily; Lambert, Kate (Children and Youth Services Review, 2018)
Objective: Maternal depression is a common, chronic set of disorders associated with significant burden to caregivers, children and families. Some evidence suggests that depression is associated with perceptions of barriers to child mental health treatment and premature termination from services. However, this relationship has not yet been examined among a predominantly low-income sample, which is at disproportionately high risk of depression, child mental health problems, and treatment drop out. Accordingly, the purpose of this study is to examine the relationships between caregiver depression and perceived barriers to treatment. Methods: Three hundred twenty (n=320) children between the ages of 7 to 11 and their caregivers were assigned to either the 4 Rs and 2Ss for Strengthening Families, which is a multiple family group intervention, or services as usual (SAU) consisting of typical outpatient mental health services. Caregiver depression was measured by the Center for Epidemiologic Depression Scale; perceived barriers to treatment were assessed via the Kazdin Barriers to Treatment Scale. Results: Clinically significant levels of depressive symptoms at baseline were significantly associated with greater scores in all four barriers to treatment subscales (stressors and obstacles competing with treatment, treatment demands and issues, perceived relevance, relationship with therapist) at post-test. Conclusions: Addressing maternal mental health, and attending to stressors that impede poverty-impacted families from child services is critical for the health and functioning of caregivers, and to ensure that children with mental health problems receive treatment.
Keywords: dept.swk; peer-reviewed

Mining for Posttraumatic Growth (PTG) in Sexual Minority Women Who Survive Intimate Partner Violence: A Conceptual Perspective. - Counselman-Carpenter, Elisabeth; Redcay, Alex (Behavioral Sciences, 2018)
This theoretical paper explores the need to use posttraumatic growth (PTG) as a framework when studying sexual minority women (SMW) who are survivors of intimate partner violence (IPV) to examine the relationship between risk factors such as stress, anxiety and alcohol use and to understand the role of protective factors through mining for the presence of posttraumatic growth (PTG). Despite a call for continued research in this highly vulnerable population, representative studies of SMW and PTG remain extremely limited. Research that examines the relationship between IPV, behavioral health issues, and posttraumatic growth would provide the opportunity to develop tailored intervention models and opportunities for program development to decrease isolation and increase factors of posttraumatic growth. In particular, the impact of how interpersonal relationships as potential mediators and/or outcomes of posttraumatic growth (PTG) needs to be explored more thoroughly. PTG is a valuable framework for vulnerable populations such as sexual minority women because it focuses on how transformative change may result from traumatic experiences such as surviving IPV.
Keywords: Intimate partner violence; Post-traumatic growth; Sexual minority women; dept.swk; intimate partner violence; peer-reviewed; sexual minority women

Barriers and facilitators to mental health screening efforts for families in pediatric primary care - Acri, Mary; Zhang, Shirley; Chomanczuk, Aminda H.; O’Brien, Kyle H; De Zitella, Maria L. Mini; Scrofani, Paige R.; Velez, Laura; Garay, Elene; Sezer, Sara; Little, Virna; Cleek, Andrew; McKay, Mary M (Journal of Family Social Work, 2018)
The purpose of this commentary was to describe the barriers and facilitators to mental health screening efforts for children between age 5 and 18 years within three primary care clinics in poverty-impacted communities as part of an integrated care model. Three screeners, two women and one male, participated in a screening effort between September and December 2015. Screeners were interviewed about their perceptions of barriers and facilitators to screening. Organizational, family, and screener-level factors were found to influence delivery of screenings to children. Given the benefits of screening in primary care settings, identifying barriers to these initiatives and ways to address them pre-emptively could potentially alter the developmental trajectory and outcomes of children at risk for serious mental health conditions. © 2018, © 2018 Taylor & Francis.
Keywords: Screening and detection efforts; article; case report; child; child mental health; clinical article; dept.rec; dept.swk; female; human; human experiment; integrated care; male; mental health; outcome assessment; peer-reviewed; perception; poverty; primary medical care

From Values to Passion to Enlivened Practice: A Palette of Possibilities - Keenan, Elizabeth (Reflections: Narratives of Professional Helping, 2018)
This narrative offers a palette of possibilities for linking micro and macro practices that arose from interviews with social workers who were viewed as addressing the profession’s dual purpose of individual well-being and social justice in their practice. I begin with my own experiences and desires to link micro and macro together as a clinical social worker and community organizer. An interlude describing the way the social workers stretched my thinking comes in between the themes. I conclude with a final reflection on the impact of their stories and implications for future research and practice.
Keywords: Macro Practice; Micro Practice; Social Justice; Well-Being; dept.swk; macro practice; peer-reviewed; social justice; social work methods; social work practice; values; ⛔ No DOI found

Multiple family group service delivery model for children with disruptive behavior disorders: Impact on caregiver stress and depressive symptoms - Gopalan, Geetha; Bornheimer, Lindsay A.; Acri, Mary; Winters, Andrew; O’Brien, Kyle H.; Chacko, Anil (Journal of Emotional and Behavioral Disorders, 2018)
Disproportionately high rates of caregiver stress and depression are found among poverty-impacted communities, with high levels of caregiver stress and depression putting youth at heightened risk for the onset and perpetuation of disruptive behavior disorders. The purpose of this study was to examine the effects of a behavioral parent training program called the 4Rs and 2Ss for Strengthening Families Program (4R2S) on caregiver stress and depressive symptoms among 320 youth aged 7 to 11 and their families assigned to either the 4R2S or services as usual (SAU) condition. Among caregivers with clinically significant (CS) scores at baseline, 4R2S participants manifested significantly reduced scores on the stress and depressive symptom scores to SAU participants at 6-month follow-up. Findings suggest that 4R2S may reduce caregiver stress and depressive symptoms among those caregivers initially manifesting CS levels of stress or depressive symptoms.
Keywords: dept.rec; dept.swk; peer-reviewed

Stigma, housing and identity after prison. - Keene, Danya E; Smoyer, Amy B; Blankenship, Kim M (The Sociological review, 2018)
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.
Keywords: Housing; Incarceration; Spatial stigma; dept.swk; peer-reviewed

Social work and hospitality: An oral history of Edith Stolzenberg - Gardella, Lorrie Greenhouse (Journal of Religion & Spirituality in Social Work: Social Thought, 2018)
Edith Richman Stolzenberg (1913–2004) was the first woman to be hired as a social worker in Hartford Public High School in Hartford, Connecticut. In a career that spanned 60 years and much of 20th-century social welfare history, she was motivated by the social justice tradition of her Jewish upbringing and the religious value of hospitality to advocate for children and families. As we enter a harsh new era for social services, this oral history explores the radical possibilities for integrating social work goals and religious values.
Keywords: adolescents; children; community; dept.swk; ethics; hospitality; oral history; religion; social work practice

An Examination of Peer-Delivered Parenting Skills Programs Across New York State - Acri, Mary C.; Craig, Nancy; Adler, Josh (Community Mental Health Journal, 2018)
Peers are an important adjunct to the public mental health service system, and are being increasingly utilized across the country as a cost-effective solution to workforce shortages. Despite the tremendous growth of peer-delivered support over the past two decades, it has only been within the past few years that peer programs have been the subject of empirical inquiry. The purpose of this study was to examine the prevalence and characteristics of peer-delivered parenting programs across the New York State public mental health service system. We surveyed 46 family peer organizations across New York State regarding their delivery of structured peer-delivered parenting programs. Thirty-four (76%) completed the questionnaire, and of them, 18 (53%) delivered a parenting program. Subsequent interviews with seven of the 18 organizations revealed peer organizations had been delivering eight unique parenting programs for upwards of two decades. Additionally, organizations offered multiple supports to families to participate. Training, supervision, and issues around fidelity are discussed, as well as the implications of this study for states utilizing a peer workforce.
Keywords: Adolescent; Behavior parent training programs; Child; Child, Preschool; Education, Nonprofessional; Humans; Infant; Infant, Newborn; Mental Health Services; New York; Parents; Peer Group; Peer support services; Peer-delivered family support; Surveys and Questionnaires; dept.swk; peer-reviewed

Waiting for shelter: Perspectives on a homeless shelter's procedures - Brown, Molly; Mihelicova, Martina; Lyons, Jennifer; DeFonzo, Jennifer; Torello, Samantha; Carrion, Andres; Ponce, Allison N. (Journal of Community Psychology, 2017)
Research on homeless shelter implementation is limited. Some shelters have lengthy waitlists, which raises important questions about implications of waitlists for individuals with immediate shelter needs. This study used qualitative methods to understand the experiences of shelter seekers who were on a shelter waitlist (N = 59), including individuals who entered the shelter from the waitlist, and those removed from the shelter waitlist for procedural reasons. The average waitlist time was nearly 3 weeks, and 22.0% stayed at least one night on the street or another public place while on the waitlist. Responses to open-ended questions regarding barriers and effectiveness of the shelter referral procedures revealed 4 themes: procedural challenges, procedural benefits, benefits of the temporary stay, and communication challenges. Further research is needed to inform shelter implementation on a larger scale in accordance with current community-wide efforts to coordinate shelter services.
Keywords: dept.swk; female; human; major clinical study; male; night; patient referral; qualitative analysis

Development of the citizens measure into a tool to guide clinical practice and its utility for case managers - Bellamy, Chyrell; Kriegel, Liat; Barrenger, Stacey L.; Klimczak, Michele; Rakfeldt, Jaak; Benson, Victoria; Baker, Michaella; Benedict, Patricia; Williamson, Bridgett; MacIntyre, Gillian (American Journal of Psychiatric Rehabilitation, 2017)
A measure of citizenship was developed and validated by Rowe and colleagues (O’Connell, Clayton, & Rowe, 2017). The items clustered around the 5 Rs of citizenship as defined by Rowe et al.: relationships, rights, resources, roles, and rights, and a sense of belonging. Although a measure has its utility in clinical settings, to address time constraints and other administrative burdens expressed by providers in their day-to-day practice, a citizens tool was developed as a practical way that providers can enhance dialogue between providers and clients on citizenship for clients served in mental health and criminal justice reentry settings. This article describes the development of the tool, testing of the tool’s utility with case managers, and implications for practice. © 2017 Taylor & Francis.
Keywords: Article; adult; case management; case manager; citizenship; clinical practice; community inclusion; community integration; dept.swk; evidence based medicine; female; human; major clinical study; male; marginalized communities; mental capacity; mental disease; mental health service; poverty; practical clinical tools; priority journal; psychological well-being; self concept; social support; socioeconomics; translational research

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education--accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education, Nursing, Baccalaureate; Educational Status; Educational Technology -- Utilization; Faculty Development; Faculty Practice; Faculty, Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools, Nursing; Self-Efficacy; Socioeconomic Factors; Students, Nursing, Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

Hungry on the inside: Prison food as concrete and symbolic punishment in a women’s prison - Smoyer, Amy B; Lopes, Giza (Punishment & Society, 2017)
Women’s perceptions of the prison experience and the punishing dimensions of their confinement are under-examined. To expand knowledge in this area, Sexton’s theory of penal consciousness is used to analyze formerly incarcerated women’s narratives about prison food. This analysis builds understanding about the lived experience of incarceration by explicating one dimension of prisoners’ understandings and perceptions of punishment. Women’s narratives describe both concrete and symbolic punishments associated with food. Participants spoke about poorly designed, sloppy food systems that left them feeling uncared for, ignored, frustrated, and humiliated. Women articulate experiences of hunger that reflect both a deprivation of adequate food and a rationing of humane attentions. These punishing perceptions may inhibit the efforts of social service and health providers to engage incarcerated and formerly incarcerated women in care. In contrast, exceptional participant narratives about positive, non-punishing food experiences suggest that ameliorated food systems could improve the lived experience of incarceration and promote the engagement in services that is needed to improve the outcomes of incarcerated and formerly incarcerated women.
Keywords: dept.swk; food; prison; punishment; women

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

A "Just Sense of Well-Being": Social Work's Unifying Purpose in Action. - Keenan, Elizabeth King; Limone, Christine; Sandoval, Silvia L (Social work, 2017)
For over a century the social work profession has had a dual purpose, to promote both human well-being and social justice, but we have not found research that explores how social workers understand and work toward both purposes across multiple practice roles and settings. Authors of this article conducted qualitative research to examine how 18 social workers in various roles and settings understand and implement both purposes in their practice. Instead of a dual purpose, participants described a unifying purpose: a "just sense of well-being" that transcends role and setting. Valuing the dignity and worth of all human beings frames and fuels their work toward a just sense of well-being through three interactive themes: challenging injustice on every level; constructing justice through relationship and resource organizing; and constructing justice through the creation of accepting environments where professionals, clients, and community members can reflect and question, and change mind-sets and actions. Participants provided an array of possibilities for action with clients, professionals, and public leaders within organizations and communities. The implication here is that social workers are charged to reinvigorate purpose and values back into practice with value-based assessment thinking that frames possibilities for action across methods and settings. Copyright © 2016 National Association of Social Workers.
Keywords: *Professional Role/px [Psychology]; *Social Justice/px [Psychology]; *Social Work/mt [Methods]; *Social Workers/px [Psychology]; Adult; Female; Humans; Male; Middle Aged; Professional Role; Qualitative Research; Social Justice; Social Work; Social Workers; Social justice; Social work practice; Values; Well-being; adult; dept.swk; dual purpose; female; human; human dignity; human experiment; leadership; male; middle aged; occupation; organization; procedures; professional standard; psychology; qualitative research; social justice; social work; social work practice; social worker; thinking; wellbeing

Responding to the oppression of addiction: Canadian social work perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2017)
Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; therapy; Social Work; Canada

Caring for the child welfare client: am I good enough? - Hoffler, Steven J (Smith College Studies in Social Work, 2017)
Given the demographics of youth served by the child welfare system, culturally responsive approaches are critical to effective social work practice and desperately needed. Like many adolescents who grow up in the child welfare system, Paul, a White adolescent male in foster care, was beset by a lack of adequate environmental resources and multiple stressors and had little hope or motivation to work on improving his situation. This article highlights the author's use of self as an African American male therapist who worked with Paul, using a Winnicottian and caring framework. Because child welfare workers are often overburdened by the demands of work, including large caseloads and clients with few to no resources, they find it difficult to consistently provide empathic and caring behaviors for their clients. The author highlights his therapeutic work and struggles with Paul and offers cultural insights and Winnicottian strategies when working with adolescents in the child welfare system who are ultimately in need of permanency and stability.
Keywords: Caring; Winnicott; child welfare; culture; dept.swk

Prison food in Denmark: Normal responsibility or ethnocentric imaginations? - Minke, Linda Kjær; Smoyer, Amy B. (Scandinavian penal history, culture and prison practice - Embraced by the welfare state?, 2017)
This book draws on historical and cross-disciplinary studies to critically examine penal practices in Scandinavia. The Nordic countries are often hailed by international observers as ‘model societies’, with egalitarian welfare policies, low rates of poverty, humane social policies and human rights...
Keywords: dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Building a bicultural bridge - Rodriguez-Keyes, Elizabeth; Piepenbring, Julie (Smith College Studies in Social Work, 2017)
The balancing act of living between two cultures can have a significant impact on the development of adolescent Latinas living in the United States. Many adolescent Latinas, particularly second generation, live with two sets of cultural values that are often in conflict with one another. This case study illustrates the importance of understanding the impact of acculturation on the individual and the family. Issues of identity, biculturalism, and bilingualismspecifically the phenomenon of language switchingare dismantled in this case study to gain deeper insight into the unique experience that second-generation Latinas undergo when negotiating two cultural orientations. These findings are important to consider when working with the Latino population as they represent one of the largest immigrant groups and the most rapidly growing group in the United States.
Keywords: Latinas; adolescent; biculturalism; bilingual psychotherapy; cultural identity; dept.swk; language switching